The (possible) effect of plain packaging on the smoking prevalence of minors in Australia: A trend analysis - Ashok Kaul; Michael Wolf (University of Zurich, Department of Economics, 2014)
A key stated objective of the Australian Plain Packaging Act 2011 is to influence smoking prevalence, in particular of minors. We use the Roy Morgan Single Source (Australia) data set on minors, (that is, Australians aged 14 to 17 years) over the time period January 2001 to December 2013 to analyze whether there is evidence that this goal has been achieved. We carry out a statistical trend analysis to study the (possible) effect of plain packaging on smoking prevalence of minors in Australia. More specifically, we fit a linear time trend that explains well the fact that observed smoking prevalence has declined steadily over the last 13 years. Two informative analyses help to draw conclusions on the (actual) effect of plain packaging on smoking prevalence of Australian minors. First, we look at the year of data before plain packaging was introduced, which happened in December 2012. Second, we compute confidence intervals around the estimated treatment effects (that is, around the deviations from the fitted trend line) from 12/2012 on. Both analyses fail to find any evidence for an actual plain packaging effect on Australians aged 14 to 17 years. Several reasonable variations to our methodology are discussed. All of these would only result in findings even more indicative of an absence of any plain packaging effect.
Additional information: See also the expert report: Methodological Report on Kaul and Wolf's Working Papers on the Effect of Plain Packaging on Smoking Prevalence in Australia and the Criticism Raised by OxyRomandie. Prof. Dr. Ben Jann, University of Berne, March 10, 2015. https://www.zora.uzh.ch/id/eprint/94280/23/Jann_2015_03_10_Methodological_Report_on_Kaul_and_Wolf59.pdf
Keywords: C13; C22; H43; I18; 330; Plain packaging; smoking prevalence; treatment effect; trend analysis